2023
DOI: 10.1158/1078-0432.ccr-22-0701
|View full text |Cite
|
Sign up to set email alerts
|

Facts and Hopes in Immunotherapy for Early-Stage Triple-Negative Breast Cancer

Abstract: A substantial fraction of early-stage triple-negative breast cancer (eTNBC) is characterized by high levels of stromal tumor-infiltrating lymphocytes (sTILs) and has a good prognosis even without systemic treatment, highlighting the importance of an endogenous anti-cancer immune response. Still, a considerable proportion of patients with eTNBC needs some ‘therapeutical push’ to kick-start this immune response. Exploiting this immune response with immune checkpoint inhibition (ICI), in combination with chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Sherene Loi was identified as the author with the highest citation count (4007), total link strength (686), and H-index, 29 while Giuseppe Curigliano had the highest number of publications 30 and G-index. 31 Table 4 presents the top 10 publishing institutions, with The University of Texas MD Anderson Cancer Center having the highest number of publications (219), Harvard Medical School receiving the highest number of citations (14490), and Dana-Farber Cancer Institute having the highest average citation count per publication (112.86). The collaboration relationships among institutions are divided into eight clusters, as shown in Figure 4(d) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sherene Loi was identified as the author with the highest citation count (4007), total link strength (686), and H-index, 29 while Giuseppe Curigliano had the highest number of publications 30 and G-index. 31 Table 4 presents the top 10 publishing institutions, with The University of Texas MD Anderson Cancer Center having the highest number of publications (219), Harvard Medical School receiving the highest number of citations (14490), and Dana-Farber Cancer Institute having the highest average citation count per publication (112.86). The collaboration relationships among institutions are divided into eight clusters, as shown in Figure 4(d) .…”
Section: Resultsmentioning
confidence: 99%
“… 52 In studies such as IMpassion-031 and KEYNOTE-522, PD-L1-positive tumor patients were associated with higher pCR rates. 31 Further analysis of the GeparNuevo study revealed TMB and immune infiltration as independent predictors of response to neoadjuvant immune checkpoint inhibition in early triple-negative breast cancer. 53 Continued development of rational and precise immunotherapy biomarkers is crucial for accurately selecting breast cancer patients who will benefit from immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have highlighted the important role of KLF2 in regulating the tumor immune microenvironment ( Rabacal et al, 2016 ; Tang et al, 2017 ; Osman et al, 2021 ; Qu et al, 2022 ), while immunotherapy represents a significant hope for breast cancer treatment ( Emens, 2018 ; Nederlof et al, 2023 ). Therefore, we analyzed the relationship between KLF2 and tumor immune infiltration in the TIMER database, and found that it was highly correlated with the expression of most immune marker proteins, and the most significant is correlated with dendritic cell immune marker genes, including CD1C, THBD and NRP1.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy has been considered as the only viable systemic treatment option for TNBC. However, recent studies showed that TNBC is more likely to benefit from immunotherapy due to its rich infiltration of lymphocytes and higher immunogenicity 6–9 . Thus far, treatment of anti‐programmed cell death 1 (PD‐1) monoclonal antibody combined with chemotherapy has shown an impressive pathological complete rate in patients with TNBC 10–12 .…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies showed that TNBC is more likely to benefit from immunotherapy due to its rich infiltration of lymphocytes and higher immunogenicity. 6 , 7 , 8 , 9 Thus far, treatment of anti‐programmed cell death 1 (PD‐1) monoclonal antibody combined with chemotherapy has shown an impressive pathological complete rate in patients with TNBC. 10 , 11 , 12 Unfortunately, based on the clinical experience of PD‐1 therapy in other cancers, a major of patients inevitably acquire therapy resistance after a period of treatment.…”
Section: Introductionmentioning
confidence: 99%